Serological diagnosis of persistent infection with Anaplasma marginale bacteria in cattle: Hasanain AJ. Al-gharban1 and Salim H. Dhahir - Al-gharban, Hasanain AJ. (The Iraqi Journal of Veterinary Medicine, 2015)
Bovine anaplasmosis is one of the tick-borne diseases caused by Anaplasma marginale bacteria which can cause high economic losses to livestock. Cattle that recovered from acute infection become carriers without clinical signs related to the disease and these bacteria can persist for lifetime in the blood. The present study was conducted to detect antibodies of persistently infected cattle with A. marginale in Wasit province/ Iraq. A total of 100 blood samples were collected randomly from cattle over one year old. Blood smears were prepared, stained with Giemsa,s stain and subjected to microscopic examination for detection of Anaplasma marginale bacteria within an infected RBCs, while serum samples were tested by a competitive enzyme - linked immunosorbent assay test (cELISA) for detection of antibodies in persistently infected cases . Mythic 18 Vet system was used as blood analysis for blood parameters measurement. Results of blood smear examination revealed 13 acute cases, while ELISA detected 35% of carriers. Whereas, the hematological parameters showed that the acutely infected cattle had the macrocytic hypochromic anemia, the persistently infected cattle displaed the microcytic hypochromic and the normocytic hypochromic anemia. Results of blood analysis revealed a significant difference (P˂0.05) in hematological parameters of acute and chronic cases. It has been concluded that cELISA is a reliable screening test for detection of antibodies specific to Anaplasma marginale bacteria.